ASPEK-ASPEK KEMAMPUAN BERPIKIR KOMPUTASIONAL DALAM PENYELESAIAN MASALAH MATEMATIKA - Dian, Mariani (Widya Warta, 2020)
Problem-solving process, according to Polya, is divided into four main stages, namely understanding the problem, determining the strategy, implementing the strategy and evaluating. Computational thinking skill is a thinking skill that is built based on the computational process conducted by humans or machines. The purpose of this research was to find the aspects of computational thinking in mathematics problem-solving. This research was literature research, while the method used in this research was descriptive-qualitative. The data that were collected and processed had computational thinking skill and problem-solving topics. The results of this research were the algorithmic thinking aspect appeared in every step of problem-solving. The logical thinking aspects appeared in understanding the problem, determining the strategy, and implementing the strategy. Efficiency and innovative thinking aspects appeared in the evaluating stage. Then, every stage in mathematics problem-solving also had the computational thinking skill aspects. The better a person's skill in each stage of the problem-solving process, then his computational thinking skills would also increase.